2011
DOI: 10.1021/ie201631q
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Quality Analysis: OpTest Fiber Quality Analyzer versus L&W Fiber Tester

Abstract: In this paper, the measurements from OpTest FQA (fiber quality analyzer) and L&W Fiber Tester were compared on 95 TMP (thermomechanical pulp) samples from a TMP-based newsprint mill in Eastern Canada that uses mixed black spruce and balsam fir as raw material. It was found that both FQA and L&W Fiber Tester provide repeatable measurements for fiber length, fines, coarseness, curl, and kink index. However, there were significant differences in the results obtained from the two instruments. Compared to FQA, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 7 publications
(9 reference statements)
1
33
0
7
Order By: Relevance
“…A few studies have shown how dissolved gas influences PLA's crystallization kinetics. [35][36][37][38][39][40][41][42] The majority of these studies confirmed that PLA's crystallization rate was enhanced by an increase in dissolved CO 2 . This was due to the plasticization effect, which reduced the dissipation energy required for the retraction of the molecules.…”
Section: Introductionmentioning
confidence: 67%
“…A few studies have shown how dissolved gas influences PLA's crystallization kinetics. [35][36][37][38][39][40][41][42] The majority of these studies confirmed that PLA's crystallization rate was enhanced by an increase in dissolved CO 2 . This was due to the plasticization effect, which reduced the dissipation energy required for the retraction of the molecules.…”
Section: Introductionmentioning
confidence: 67%
“…The film was presumably formed of extracellular material including polysaccharides and extractives, as well as very fine cellulosic fibrils produced after high-energy refining. The pulp fines and fibrils were probably generated from the primary wall and outer secondary wall (Li et al 2011a). The increased pulp fines and fibrils can lead to the increase of specific surface area of pulp fibres (Li et al 2011b), thus increasing the bonding potential (i.e.…”
Section: Effects Of Refining On the Surface Morphologymentioning
confidence: 99%
“…One way of generating these data is the time-consuming process of manually measuring cells from physically and chemically macerated wood under a light microscope [Fujiwara and Yang, 2000]. Alternatively, optical fibre analysers are used, which allow a rapid and automated analysis of samples, and this technique has been used to build up a picture of fibre geometry across different species [Li et al, 2011, Mvolo et al, 2015 and throughout a complete tree [Yemele et al, 2015]. These studies show that cell length varies from the centre of the tree, increasing through the juvenile wood and becoming relatively constant in mature wood.…”
Section: Background and Summarymentioning
confidence: 99%
“…These studies show that cell length varies from the centre of the tree, increasing through the juvenile wood and becoming relatively constant in mature wood. Fibre analysers operate on wood pulp, thus losing the structure and arrangement of the material before measurement [Li et al, 2011]. µCT scanning offers the opportunity to rapidly measure the geometry of hundreds of cells throughout a volume of intact wood.…”
Section: Background and Summarymentioning
confidence: 99%